61.9k views
5 votes
Lily solved the equation 3x − 10 = -3x + 8. The explanation of her process is shown. Select the text that shows an error in her process or justification of steps, if one exists

2 Answers

5 votes

Answer:

I used the subtraction property of equality to achieve the solution of x = 3.

Explanation:

Lily’s process of solving the equation is correct until step 3. To achieve the solution, the division property of equality is used.

User Thatismatt
by
5.3k points
4 votes

3x - 10 = -3x + 8

Add 3x to both sides

6x - 10 = 8

Add 10 to both sides

6x = 18

Divide both sides by 6

x = 3

User Hwschuur
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.